INFLUENCE OF FLUOXETINE ON PHARMACOKINETICS AND PHARMACODYNAMICS OF GLIBENCLAMIDE IN DIABETIC RATS - Meraj, Tahseen; MUNWAR KHATOON; REDDY, A.RAMA NARSIMHA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: The aim of the present study was to evaluate the influence of Fluoxetine (antidepressant drug) on pharmacokinetic and pharmacodynamics of Glibenclamide (antidiabetic drug) in diabetic rats. Methods: Alloxan-induced Diabetic model in rats has been used in this study. After induction of diabetes, Glibenclamide (10mg/kg/p.o or 5mg/kg/p.o) and Fluoxetine (5.4mg/kg/p.o) were administered orally for 7days. The Pharmacokinetic parameters like t1/2, AUC, Clearance, Tmax and Cmax of Glibenclamide, with and without combination of Fluoxetine treatment were determined. The blood glucose levels were estimated using Glucose Oxidase-Peroxidase(GOD-POD) method. Results: The increase in Glibenclamide concentration might be due to interaction with Fluoxetine at metabolic enzyme (CYP 3A4 ,CYP 2D6 and CYP 2C19 Isoenzymes). Increase in plasma concentration increases AUC of Gibenclamide indicates the raised bioavailability in presence of Fluoxetine.Glibenclamide treatment in combination with Fluoxetine has shown significant decrease in Blood Glucose Levels when compared to rats treated with Glibenclamide. The results of the present study indicated that Fluoxetine has influence on Pharmacokinetic and Pharmacodynamics of Glibenclamide. Thus concluding the concomitant administration of Glibenclamide and Fluoxetine should be used in caution. Further studies are to be done to reduce the dose of glibenclamide (antidiabetic drug) when it is given in combination with fluoxetine (antidepressant drug ) Keywords: Glibenclamide, Fluoxetine, Pharmacokinetics, Pharmacodynamics, Diabetes